2017
DOI: 10.1038/srep42701
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide Attenuates Acute Kidney Injury after Hepatic Ischemia and Reperfusion by Enhancing Autophagy

Abstract: Octreotide exerts a protective effect in hepatic ischemia-reperfusion (HIR) injury. However, whether octreotide preconditioning could also reduce acute kidney injury (AKI) after HIR is unknown. This study was designed to investigate the role of octreotide in AKI after HIR. Male Sprague-Dawley rats were pretreated with octreotide or octreotide combined with 3-methyladenine (autophagy inhibitor, 3MA). Plasma creatinine, inflammation markers (e.g., TNF-α and IL-6 etc.), apoptosis, autophagy and phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…This positive effect of OCT on autophagy is coupled to the OCT well-known antiapoptotic actions, since our results demonstrate that the anti-apoptotic efficacy of OCT is completely abolished when the autophagic flux is blocked by CQ. Interestingly, OCT has been recently found to exert protective effects in the kidney after hepatic ischemia through induction of autophagy [61]. A wide variety of data support the notion that autophagy plays a fundamental role in preventing neurodegeneration [22,62,63], and perturbations of autophagy are thought to participate to the pathogenesis of all major neurodegenerative diseases [64,65].…”
Section: Autophagy and Oct-mediated Neuroprotection In Drmentioning
confidence: 99%
“…This positive effect of OCT on autophagy is coupled to the OCT well-known antiapoptotic actions, since our results demonstrate that the anti-apoptotic efficacy of OCT is completely abolished when the autophagic flux is blocked by CQ. Interestingly, OCT has been recently found to exert protective effects in the kidney after hepatic ischemia through induction of autophagy [61]. A wide variety of data support the notion that autophagy plays a fundamental role in preventing neurodegeneration [22,62,63], and perturbations of autophagy are thought to participate to the pathogenesis of all major neurodegenerative diseases [64,65].…”
Section: Autophagy and Oct-mediated Neuroprotection In Drmentioning
confidence: 99%
“…The model of renal injury after liver I/R injury was done as mentioned before in previous research [5,14] in which the liver I/R injury was first implemented. Briefly, rats in our experiment were anesthetized and subjected to a midline laparotomy under aseptic condition.…”
Section: Model Of Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Prolonged liver ischemia followed by reperfusion stimulates the induction of pro-inflammatory cytokines as well as the reactive oxygen species (ROS) leading to hepatic cell as well as remote organ injury accompanied with high morbidity and mortality [3,4]. The injury induced by liver ischemia/reperfusion (I/R) in lung and kidney has been reported [5,6]. However, the exact mechanism underlying the renal injury induced by liver I/R has not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/AKt/mTOR pathway is of great importance to the development, progression and treatment of HCC. It has been reported that TNF-α and IL-6 induced VEGF expression and angiogenesis can be significantly inhibited by rapamycin, indicating that mTOR plays an important role in inflammationinduced angiogenesis [50] . Inflammatory factors such as TNF-α, IL-6, IL-1β and other secretions are also regulated by mTOR signaling pathway [51] .…”
Section: Signaling Pathwaysmentioning
confidence: 99%